1990
DOI: 10.1152/jappl.1990.68.2.748
|View full text |Cite
|
Sign up to set email alerts
|

Energy expenditure during bicycling

Abstract: This study was designed to measure the O2 uptake (VO2) of cyclists while they rode outdoors at speeds from 32 to 40 km/h. Regression analyses of data from 92 trials using the same wheels, tires, and tire pressure with the cyclists riding in their preferred gear and in an aerodynamic position indicated the best equation (r = 0.84) to estimate VO2 in liters per minute VO2 = -4.50 + 0.17 rider speed + 0.052 wind speed + 0.022 rider weight where rider and wind speed are expressed in kilometers per hour and rider w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
85
1
2

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(93 citation statements)
references
References 0 publications
5
85
1
2
Order By: Relevance
“…These findings confirm that rHuEPO doping provides a significant physiological advantage consistent with the increase in road cycling performance shown in the present study. Cycling speed and VO2max are correlated in road cycling (McCole, Claney, Conte, Anderson, & Hagberg, 1990), as in all other aerobic sports (track and field, middle-and long-distance running, cross-country skiing, rowing; Seiler, 2006). In a previous study, McCole et al (1990) showed that an increase in speed from 37.5 to 40 km • h -1 may be related to a 7.5% increase in VO2max.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These findings confirm that rHuEPO doping provides a significant physiological advantage consistent with the increase in road cycling performance shown in the present study. Cycling speed and VO2max are correlated in road cycling (McCole, Claney, Conte, Anderson, & Hagberg, 1990), as in all other aerobic sports (track and field, middle-and long-distance running, cross-country skiing, rowing; Seiler, 2006). In a previous study, McCole et al (1990) showed that an increase in speed from 37.5 to 40 km • h -1 may be related to a 7.5% increase in VO2max.…”
Section: Discussionmentioning
confidence: 98%
“…Cycling speed and VO2max are correlated in road cycling (McCole, Claney, Conte, Anderson, & Hagberg, 1990), as in all other aerobic sports (track and field, middle-and long-distance running, cross-country skiing, rowing; Seiler, 2006). In a previous study, McCole et al (1990) showed that an increase in speed from 37.5 to 40 km • h -1 may be related to a 7.5% increase in VO2max. The expected effect on VO2max has been the major incentive to use EPO in aerobic sports since its discovery.…”
Section: Discussionmentioning
confidence: 98%
“…19,20 Drafting is not as common in cyclocross because the technique is not as beneficial at lower speeds and because it is difficult to perform on varied terrain. 21 The relative speed in cyclocross is lower than speeds found on the road due to the increased rolling resistance of the terrain and the need to navigate through obstacles and/or turns in the course. Because of the difference in drafting, cyclocross is a related but different sport than road or criterium racing, defined much less by teamwork and therefore effort sharing.…”
Section: Discussionmentioning
confidence: 99%
“…While most aerodynamic studies in cycling focused on the aerodynamic drag of a single (isolated) cyclist, several efforts have also been made to assess the effects of "drafting" [2,[15][16][17][18][19][20][21][22]. In drafting, two or more cyclists ride close behind each other to reduce aerodynamic drag.…”
Section: Introductionmentioning
confidence: 99%
“…From windtunnel runs and coast-down tests, Kyle and Burke [2] observed that air resistance is decreased about 40% for the drafting riders. McCole et al [16] measured the O 2 uptake of cyclists riding outdoors at speeds from 32 to 40 km/h. They found that drafting at 32 km/h reduced VO 2 (i.e.…”
Section: Introductionmentioning
confidence: 99%